The Influence of Perceptions of Tax Understanding, Benefits of NPWP and Tax Sanctions on Individual Taxpayer Compliance - Neng Asiah; Sabaruddinsah; Widya Purnama Sari (Journal of Research in Business, Economics, and Education, 2021)
The purpose of this study was to determine the perception of understanding of taxation, the benefits of NPWP and tax sanctions on individual taxpayer compliance. This type of research uses quantitative research. The sample used in this study were 100 respondents of individual taxpayers registered at KPP Pratama South Cikarang. Sources of data used in this study are primary data and secondary data. The data used in this study were obtained from the results of distributing questionnaires to individual taxpayers in South Cikarang. The data analysis technique in this study used descriptive statistics as intended to give general conclusions. The data analysis method uses validity test, reliability test, classical assumption test, multiple linear regression test with the help of SPSS software. The results of the study explain that the understanding of taxation does not affect the compliance of individual taxpayers, the benefits of NPWP do not affect the compliance of individual taxpayers, tax sanctions affect the compliance of individual taxpayers as well as the simultaneous influence of perceptions of understanding of taxation, the benefits of NPWP, and tax sanctions. towards individual taxpayer compliance.